1982
DOI: 10.1515/hfsg.1982.36.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Holz-Kunststoff-Kombinationen hoher Zähigkeit und Feuchteformbeständigkeit

Abstract: Schlüsselwörter (Sachgebiete) Holz-Kunststoff-Kombinationen (Polymerholz) Acrylgruppenhaltige Isocyanate Methylmethacrylat Gammabestrahlung Härte Schlagbiegefestigkeit Wasseraufnahme Räumliches Queilmaß Zusammenfassung Mit acrylgruppenhaltigen Isocyanatverbindungen und Methylmethacrylat als Imprägniermittel sowie Gammastrahlungshärtung können Holz-Kunststoff-Kombinationen hergestellt werden, die sich gegenüber anderen Kombinationen insbesondere durch ihre hohe Feuchteformbeständigkeit und ihre hohe Zähigkeit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…From the above it was observed that all the elastic moduli increased, the values of which differed widely depending on the specimen, the monomer used and the level of polymer loading. Such trends have been reported earlier (Mayer 1981;Schaudy et al 1982;Brebner et al 1985). The difference in the moisture content of the starting wood sample was not found to influence the mechanical properties significantly.…”
Section: Radiation Dose For Polymerizationsupporting
confidence: 87%
“…From the above it was observed that all the elastic moduli increased, the values of which differed widely depending on the specimen, the monomer used and the level of polymer loading. Such trends have been reported earlier (Mayer 1981;Schaudy et al 1982;Brebner et al 1985). The difference in the moisture content of the starting wood sample was not found to influence the mechanical properties significantly.…”
Section: Radiation Dose For Polymerizationsupporting
confidence: 87%
“…At normal temperature this seems to be unlikely. It was therefore surprising that a mixture of this type led to WPC with high impact bending and low volumetric swelling at normal irradiation conditions (Schaudy et al, 1982). The results were even better when a reaction product of diisocyanate and hyroxy-(meth)acrylate or another compound with one isocyanate group and one (meth) acrylic group in the same molecule was used.…”
Section: Improvement Of Toughness (Reduction Of Brittleness)mentioning
confidence: 99%